Training on Increasing and Developing the Quantity of Sheep in Improving the Economic Welfare of Farmers in Jenggawah Village - Yulianto, Roni; Himmatul Khasanah Nur Widodo; Desy Cahya Widianingrum (Faculty of Mathematics and Natural Sciences, University of Jember. Jl. Kalimantan No.37, Krajan Timur, Jemberlor, Kec. Sumbersari, Jember Regency, East Java 68121, 2024)
Jenggawah Village has extensive agricultural land and plantations, especially rice, corn and coffee crops whose waste has not been utilized. The potential of Jenggawah Village, Jember Regency is very potential for development in the agricultural sector. Innovations for utilizing agricultural waste can be used to process agricultural waste as animal feed and livestock waste to be used as organic fertilizer, which is a superior environmentally friendly product that has great potential and can improve the economy of farmers from product sales. The objectives of this service activity are: 1) providing assistance from educational related agencies in optimizing the increase and development of the quantity of sheep livestock, 2) conducting training and management of sheep farming business development, 3) creating product innovations using rice straw biotechnology to improve the nutritional quality of sheep feed. The target of this service program is: together with the Jenggawah village government, we can empower farmers and breeders in fermented straw processing so that they can realize the independence and welfare of breeders in reducing feed production costs, so that they can reduce feed production costs and increase breeder profits by utilizing feed biotechnology innovations. ruminant livestock. The conclusion of this service activity is: increasing sheep production can be increased by utilizing biotechnological innovations in animal feed from rice straw waste fermentation, and can minimize feed costs, so that this opportunity can increase the income and welfare of farmers